A survey on an important inequality to Fractional Differential Equations - Carvalho Neto, Paulo Mendes de (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2022)
This work aims to present and discuss a differential inequality involving Caputo and Riemann-Liouville fractional derivatives, which have proved to be very useful to the study of timedependent partial differential equations with time fractional derivatives.